2000
DOI: 10.1161/01.cir.101.6.624
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic Efficacy of Dipyridamole in Treatment of Reperfusion Arrhythmias

Abstract: Background-Intracellular calcium overload is believed to play an important role in development of reperfusion arrhythmias. Dipyridamole, an inhibitor of cellular uptake of adenosine, may prevent or terminate reperfusion arrhythmias by reducing intracellular calcium overload. Methods and Results-First, we tested for a preventive effect of dipyridamole. Sixty-one patients who underwent primary PTCA for treatment of acute anterior wall myocardial infarction were enrolled in this prospective study. Patients were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 43 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…In a canine model of hypothermia, dipyridamole is thought to mediate such effect (110) and reduced the core temperature of which dogs would go into VF (111).…”
Section: Other Pharmacological Agentsmentioning
confidence: 99%
“…In a canine model of hypothermia, dipyridamole is thought to mediate such effect (110) and reduced the core temperature of which dogs would go into VF (111).…”
Section: Other Pharmacological Agentsmentioning
confidence: 99%
“…Furthermore, intracoronary DIP reduced the incidence of adverse cardiovascular events in the first 48 h after balloon angioplasty of small coronary arteries [7]. Yoshida and colleagues [8] also reported that intracoronary DIP administered for acute anterior wall MI before primary percutaneous coronary intervention prevented reperfusion arrhythmia. However, in a study by Thompson and colleagues [9], 202 patients with ST-segment elevation myocardial infarction (STEMI) who were randomly assigned to receive either a continuous intravenous heparin infusion or oral DIP (100 mg, 3 times a day) and ASA (300 mg/d) 24 h after thrombolytic therapy had similar outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine is of particular interest because of its wide-ranging effects on multiple organ systems by interacting with adenosine receptors Adora1, Adora2a, Adora2b, and Adora3 (1, 18, 19) which govern cellular functions via regulation of downstream heterotrimeric G-proteins (20, 21). ENTs also modulate efficacy for a chemically diverse range of therapeutics (>30 FDA/EMA approved drugs) including anticancer (e.g., gemcitabine, cytarabine) (22), antiarrhythmia (e.g., dilazep, dipyridamole) (23, 24), antiviral (e.g., ribavirin, azidothymidine) (2527), and antihypertensive (e.g., nifedipine) (28, 29) medications (Figure 1). However, medications that exert their effects in the cardiovasuclar (e.g., dilazep, dipyridamole, nifedipine) system are known to have overlapping functions and can affect vasodilation (3336) as well as platelet activity (37–40).…”
mentioning
confidence: 99%